Distance Learning in the Humanitarian Field amid the Coronavirus Pandemic: Risks of Creating Barriers and Innovative Benefits - Aleхandrovich Glebov, Viktor (2021)
The goal of the research is to study the risks and innovative benefits of distance learning. The main research method is an anonymous survey of academic staff (university teachers) and students (future philologists, foreign language teachers), based on the need to clarify the situation associated with the use of distance learning technologies in the conditions of the quarantine. The following data have been obtained in the course of the study: the most significant opportunities for distance learning, the level of satisfaction with distance learning technologies, the compliance with the previously drawn up training schedule in the distance learning conditions, the satisfaction with the promptness of informing about the training schedule, the use of distance learning technologies to provide feedback, the factors that affect the quality of the implementation of distance learning technologies, the teachers' positive experience of using distance learning technologies, the use of distance learning technologies when providing students with lecture materials, as well as the use of information resources of the institution by the students. The results of the study have revealed that both students and teachers are aware of the need to work in a distance learning environment, but the coronavirus pandemic has created new risks for the higher education system, which require an innovative approach to overcoming barriers in the distance learning system. The results of the article can be used in the organization of distance learning at a humanitarian university.